The biggest snowman ever - Kroll, Steven; Bassett, Jeni (New York : Scholastic, Inc., 2005)
When the mayor of Mouseville announces a contest, Clayton and Desmond compete to win the prize for building the biggest snowman.
"Cartwheel books."
4-8 yrs.
Keywords: Snowmen -- Fiction; Mice -- Fiction; Contests -- Fiction; Cooperativeness -- Fiction; Fiction